Expansion of tumor-infiltrating lymphocytes (TIL) from human pancreatic tumors. Issue 1 (December 2016) - Hall, MacLean; Liu, Hao; Malafa, Mokenge; Centeno, Barbara; Hodul, Pamela; Pimiento, José; Pilon-Thomas, Shari; Sarnaik, Amod
Abstract Background We evaluated whether tumor infiltrating lymphocytes (TIL) could be expanded from surgically resected tumors from pancreatic cancer patients. Methods Tumors were resected from pancreatic cancer patients. Tumors were minced into fragments and cultured in media containing high dose interleukin-2 (IL-2) for up to 6 weeks. T cell phenotype, activation markers, and reactivity were measured. Results TIL expansion was measured in 19 patient samples. The majority of these TIL were CD4+ T cells and were highly activated. Purified CD8+ T cells produced IFN-γ in response to HLA-matched pancreatic tumor targets. PD-1 blockade and 4-1BB stimulation were demonstrated as effective strategies to improve effective TIL yield, including the production of tumor-reactive pancreatic TIL. Conclusions TIL expanded from pancreatic tumors are functional and able to respond to pancreatic tumor associated antigens. PD-1 blockade, 41BB stimulation, and CD8+ T cell enrichment are effective strategies to improve TIL yield and tumor reactivity. These results support the development of adoptive cell therapy strategies using TIL for the treatment of pancreatic cancer.